2016
DOI: 10.1080/02770903.2016.1201835
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences underlying self-management and reporting of symptoms in teens with asthma

Abstract: Background Teens often have inadequate asthma self-management and control. However, little is known of their perceptions of or rationales for self-management behaviors. Objectives To explore how teens self-manage asthma, including experiences, perceptions, responses to and reporting of symptoms. Methods A case-based, qualitative-descriptive design was used. Data were collected from minority and non-minority teens with controlled and uncontrolled asthma and their respective parents (N=28). There were four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 35 publications
3
65
0
Order By: Relevance
“…Furthermore, while assessing ED visits and hospitalization is undoubtedly essential, our findings suggest that absence of acute healthcare utilization might not be a sufficient indicator of well controlled asthma, particularly in adolescent patients who tend to tolerate high levels of symptoms without reporting or responding. 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while assessing ED visits and hospitalization is undoubtedly essential, our findings suggest that absence of acute healthcare utilization might not be a sufficient indicator of well controlled asthma, particularly in adolescent patients who tend to tolerate high levels of symptoms without reporting or responding. 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent qualitative study explored self‐management of asthma in adolescents and included parent perspectives. Adolescents often neglected to report normal asthma symptoms to parents, which was linked to subsequent lack of symptom reporting to healthcare professionals (HCPs) . Much of the existing literature is focused on the adolescent yet we argue that any successful intervention to improve their self‐management would benefit from understanding the current perspective of parents and HCPs.…”
Section: Introductionmentioning
confidence: 95%
“…Adolescents often neglected to report normal asthma symptoms to parents, which was linked to subsequent lack of symptom reporting to healthcare professionals (HCPs). 7 Much of the existing literature is focused on the adolescent yet we argue that any successful intervention to improve their self-management would benefit from understanding the current perspective of parents and HCPs. Firstly because they may have a different understanding of the factors that influence adolescents self-management, compared to adolescents themselves, and secondly to understand whether the support that parents and HCPs provide is aligned with the adolescent's needs and expectations.…”
Section: Introductionmentioning
confidence: 99%
“…A further possible reason for non-adherence is over-estimation of control. Mammen et al [15] reported that teenagers with uncontrolled asthma tend to normalise their symptoms and have higher treatment thresholds. Similarly, we found that in students with suboptimal control, 42.3% considered that their asthma was either 'well' or 'completely controlled' .…”
Section: Discussionmentioning
confidence: 99%